Training Introduction to Digital Image Processing Techniques in The Medical Field - Rika Rosnelly; Linda Wahyuni; Hardianto Hardianto; Elsa Aditya (STMIK Pontianak, 2022)
Malaria is a health problem in Asia, especially in Indonesia. Malaria is an infectious disease, through the bite of a female Anopheles mosquito. Data sourced from the Ministry of Health of the Republic of Indonesia, there are 261,671 cases of malaria in Indonesia, one hundred of which claimed human lives. There are 28% in Indonesia living in malaria endemic areas for low, medium and highlands. Medical examination takes a long time, one example for examination of malaria parasites is with a microscope. The examination microscope has a hundred fields of view. Digital image processing is an image manipulation process to get better image results. The stages begin with ROI (Region of Interest), image improvement, segmentation with Otsu thresholding, extraction of shape and texture features and classification using LVQ. Digital image processing can help in the medical field, especially for disease identification.